The Role of Law in Improving Financial Literacy in Online Lending in the Context of Development Economic Law - Nurhilmiyah; Purba, Hasim; Sitompul, Zulkarnain; Azwar, T. Keizerina Devi (Ultimate Journal of Legal Studies, 2023)
Law is believed to be able to provide changes towards improving the nation's economy, and can also be a tool to engineer people's behavior in achieving their welfare. One of them is by increasing financial literacy in the field of online loans in the context of development economic law. In recent years since the mushrooming of information technology-based lending and borrowing service providers (LPB2TI) in Indonesia, there have been many legal events related to this online lending and borrowing transaction. Starting from the imposition of loan interest that exceeds the upper limit as determined by the strategic partner of the Financial Services Authority in this case appointed is the Indonesian Fintech Joint Funding Association (APFI), to the low public knowledge about their rights and obligations in the legal relationship of creditors or investors, information technology-based lending and borrowing service providers, and debtors or online loan customers. This is what makes writing this topic very important to pay attention to. In order to elaborate the role of law in increasing inclusive financial literacy in online loans in the context of Economic Development Law.